Multiple eruptive milia in chronic graft versus host disease: A case report - Alamoudi, Loujen; AlShehri, Abdulrahman; Al-Zaid, Tariq; Al-Faky, Yasser (Indian Journal of Case Reports, 2026)
Graft-versus-host disease (GVHD) is a significant immunological complication that commonly arises after allogeneic hematopoietic cell transplantation. While cutaneous manifestations of GVHD are well recognized, multiple eruptive milia are an unusual manifestation of cutaneous chronic GVHD. We report a case of periorbital milia developing in a 10-year-old child with chronic GVHD following allogeneic hematopoietic stem cell transplantation. This case illustrates an uncommon cutaneous manifestation of chronic GVHD, in which immune-mediated epidermal disruption may contribute to secondary milia formation.